The Relationship Between Employees Turnover Intention And Sexual Harassment At Workplace - Zafirah, Osman (Universiti Malaysia Sarawak (UNIMAS), 2020)
This study is aimed at finding the relationship between employees’ turnover intention and sexual harassment at workplace (absenteeism, job satisfaction, and psychological stress). This research was done by using quantitative method where the data were collected by using questionnaire as the instrument. The data was collected from 66 samples in one of the private organisations in Kuching, Sarawak. The data were then analysed using both descriptive and inferential statistics. Besides, Pearson Correlation test procedure was used to measure the relationship between the independent variables and dependent variables. The findings have shown that there is significant relationship between employees’ turnover intention and sexual harassment at workplace. It was found that absenteeism is the dominant factor affecting employees’ turnover intention. As such, the researcher has recommended a focus on the study that may guide the organisations in the future researches.